Comparison of solar based closed loop DC-DC converter using PID and ANN control for shunt motor drive - S. Jayaprakash; R. Ramani; M. Kavitha; V. Senthil Nayagam (Institute of Advanced Engineering and Science, 2019)
This paper explained details of Comparison of solar based closed loop DC -DC converter using PID and ANN Control for Shunt motor drive. Solar panel output is given to full bridge converter, stepup transformer, full wave converter, ∏ filter and Shunt motor drive are connected.Comparator compare the set value and the output signal of the motor produce a signal, based on the signal, full wave conveter produce the voltage to run the motor, Speed of motor,Torque and Armature current,Rise time,Peak time, Settling time and Steady state error are measured and evaluated by experimental.A circuit operation and simulation designed for a 1000 RPM speed of shunt motor arrived and tested.